Short Communication: Diffusion Tensor Anisotropy in the Cingulate in Borderline and Schizotypal Personality Disorder - Goldstein, Kim E. (Psychiatry Res, 2019)
Despite nosological differences between borderline personality disorder (BPD) and schizotypal personality disorder (SPD), research increasingly provides evidence of BPD difficulty with symptoms that are typically ascribed to patients with SPD (e.g., disturbed cognitions). We examined the cingulate, a brain region implicated in the pathophysiology of both disorders, to determine similarities/differences between the groups, and similarities/differences from healthy controls (HC’s). 3T structural and diffusion tensor magnetic resonance imaging scans were acquired in BPD (n=27), SPD (n=32), HC’s (n=34). Results revealed that BPD patients exhibited significantly lower FA in posterior cingulate white matter compared to HC’s (p=0.04), but SPD patients did not.